RAPID SCREENING OF PHYTOPATHOGENIC Erwinia sp. OF TWO POTATO VARIETIES (SPUNTA AND DESIREE) FROM ALGERIAN AGRICULTURAL FIELDS - Mokrani, Slimane; Nabti, El-hafid (Universitas Lampung, 2021)
Rapid screening of phytopathogenic Erwinia sp. of two potato varieties (Spunta and Desiree) from Algerian agricultural fileds. Isolation, phenotypic identification and in vitro phytopathogenicity screening of Erwinia sp. from agricultural field of two potato varieties (Spunta and Desiree) in Algeria. The current study aims to isolate, identify and screen phytopathogenic isolates of Erwinia sp. causing potato diseases. The techniques presented in this study for isolation and characterization of phytopathogenic Erwinia sp. are conventional methods that are used in this field of research. Seven phytopathogenic bacteria were recovered from potato tubers of two varieties (Spunta and Desiree). The phenotypic identification allowed characterizing typical colonies of Erwinia sp. on two semi-selective media: King’s B and TCC media. Erwinia sp. formed characteristic colonies on King’s B medium that were round, convex and representing creamy color. While, Erwinia sp. also developed specific colonies on TCC medium which were pale purple, circular, convex, even bulging; smooth and mucous. In vitro phytopathogenicity test on potato slices lead to screen the phytopathogenic isolate E5 characterized by highest rotten tissue zone of (2.33 ± 0.29 cm) and (2.33 ± 0.58 cm) toward Spunta and Desiree varieties, respectively. Followed, by isolate E4 characterized by rotten tissue zone of (1.83 ± 0.58 cm) and (2.17 ± 0.29 cm) toward Spunta and Desiree varieties, respectively; compared to their corresponding uninfected controls. The RTZ (Rotten tissue zone) evidently is proportional to the specific pathogenicity of Erwinia sp. isolates and the characteristic sensitivity of various varieties (Spunta and Desiree). Thus, make determining RTZ a rapid screening technique for the selection of the highest phytopathogenic isolates. This investigation provides valuable information for rapid screening (infected potato tuber) and characterization (isolation using semi-selective media) of pathogenic Erwinia sp. engendering potato disease compared to existing methods like infection of leaves or plants; and phytopathogenic Erwinia sp. identification through PCR amplification or in situ hybridation.